Incidence and Clinical Significance of Positional Downbeat Nystagmus in Posterior Canal Benign Paroxysmal Positional Vertigo - Oh, Eun Hye (J Clin Neurol, 2019)
BACKGROUND AND PURPOSE: The aim of this study was to determine the incidence and clinical significance of positional downbeat nystagmus (pDBN) after treatment of posterior canal (PC) benign paroxysmal positional vertigo (BPPV). METHODS: We recruited 77 patients with a diagnosis of PC BPPV, and assessed the presence of pDBN during follow-up positional tests after performing the Epley maneuver. RESULTS: An immediate response to the Epley maneuver was exhibited by 57 of the 77 patients, with resolution of their positional torsional upbeat nystagmus (pT-UBN). Twenty-two (39%) of them exhibited pDBN during follow-up tests performed 1 hour later. The latency and duration of pDBN were 3.2±2.0 and 12.0±10.0 s (mean±SD), respectively. The maximum slowphase velocity of pDBN was 5.1±2.5 degrees, and ranged from 2.0 to 12.2 degrees. A torsional component was also observed in six patients. The patients with pDBN were much more likely to develop a typical form of PC BPPV again at a 1-week follow-up (5/22, 23%) compared to those without pDBN (1/31, 3%; p=0.036). pDBN disappeared in all patients within 6 months. CONCLUSIONS: Our study found transient pDBN in 40% of patients with PC BPPV after the immediate resolution of positional vertigo and pT-UBN. pDBN may be attributed to residual debris in the distal portion of the PC, which can move toward the ampulla producing an ampullopetal flow of endolymph during positioning.